2016
DOI: 10.5194/tc-2016-229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resolution capacity of geophysical monitoring regarding permafrost degradation induced by hydrological processes

Abstract: Abstract. Geophysical methods are often used to characterise and monitor the subsurface composition of permafrost. The resolution capacity of standard methods, i.e. Electrical Resistivity Tomography and Refraction Seismic Tomography, depends hereby not only on static parameters such as measurement geometry, but also on the temporal variability in the contrast of the geophysical variables (electrical resistivity and P-wave velocity). Our study analyses the resolution capacity of Electrical Resistivity Tomograph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In combination with the large spatial coverage of the conducted 2-D geophysical surveys, this approach is considered to yield plausible ranges of ice and water contents for the whole rock glacier. Previous studies applying and testing the 4PM on rock glaciers showed that estimated ice and water contents can be reasonable well delineated and are in good agreement with nearby boreholes and complementary data sets 520 (Hauck et al, 2011;Mewes et al, 2017;Schneider et al, 2013).…”
Section: Geophysical Approachsupporting
confidence: 63%
See 3 more Smart Citations
“…In combination with the large spatial coverage of the conducted 2-D geophysical surveys, this approach is considered to yield plausible ranges of ice and water contents for the whole rock glacier. Previous studies applying and testing the 4PM on rock glaciers showed that estimated ice and water contents can be reasonable well delineated and are in good agreement with nearby boreholes and complementary data sets 520 (Hauck et al, 2011;Mewes et al, 2017;Schneider et al, 2013).…”
Section: Geophysical Approachsupporting
confidence: 63%
“…In addition, the spatial resolution of the geophysical approach depends on the sensor spacing in the field in relation to the dimension of the observed layers and 525 anomalies causing a trade-off between the spatial coverage of the landform (profile length and investigation depth) and the resolution capacity for small scale structures in the model domain. Mewes et al (2017) showed that the resolution capacity of the 4PM is suitable to detect hydrological structures and permafrost degradation in rock glaciers with sensor spacings comparable to the spacings used in this study (Tables 2, 3). However they empasize that the resolution capacity of vertical https://doi.org/10.5194/tc-2020-29 Preprint.…”
Section: Geophysical Approachmentioning
confidence: 59%
See 2 more Smart Citations
“…Geophysical measurements appear to be the most efficient approach to gain such in situ data (Mewes et al, 2016) and we consider that the use of geophysical results to parameterise complex thermal modelling approaches is one of the future challenges. This will constitute a first step in modelling the thermohydromechanical processes leading to bedrock failure.…”
Section: Perspectivesmentioning
confidence: 99%